2002
DOI: 10.1176/appi.ajp.159.6.941
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Posttraumatic Distress in Hospitalized Trauma Survivors With Acute Injuries

Abstract: Clinical and demographic characteristics readily identifiable at the time of surgical inpatient hospitalization predict PTSD symptoms over the year after injury. Effectiveness trials that test screening and intervention procedures for at-risk inpatients should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
3
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 183 publications
(140 citation statements)
references
References 42 publications
7
124
3
6
Order By: Relevance
“…In a study on subjects after motor vehicle accidents or violent assault by Zatzick et al (Zatzick et al, 2002) PD did not significantly explain the development of PTSD severity over 1 year over and above other variables in a random coefficient regression model.…”
Section: Studies With Negative Outcomesmentioning
confidence: 83%
See 1 more Smart Citation
“…In a study on subjects after motor vehicle accidents or violent assault by Zatzick et al (Zatzick et al, 2002) PD did not significantly explain the development of PTSD severity over 1 year over and above other variables in a random coefficient regression model.…”
Section: Studies With Negative Outcomesmentioning
confidence: 83%
“…Two studies utilized an observer-rated version (Wittmann et al, 2006;Zatzick, Kang, Muller, Russo, Rivara, Katon, Jurkovich, & Roy-Byrne, 2002). Assessments of PD occurred within a week of the trauma in 10 studies.…”
Section: General Characteristics Of the Studiesmentioning
confidence: 99%
“…The present study is one of a few that address comorbidity between AUD and PTSD symptoms over time in acute trauma samples (Acierno et al, 1999;Zatzick et al, 2002). Guided by previous work indicating increased risk for PTSD in women who had previous AUD (Acierno et al, 1999;Cottler et al, 1992), we focused our analyses on whether lifetime AUD and alcohol problems were related to chronicity of PTSD symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…2,24,33 Physical injury as the result of a traumatic event increases the risk for experiencing psychiatric symptoms, including depression and post-traumatic stress disorder (PTSD), as well as other psychosomatic symptoms, or those without any known medical cause. 6,8,10,11,18,13,20,22,43,48,51,52,54,49 In analysis of data from the National Study on the Costs and Outcomes of Trauma (NSCOT), the largest study to date assessing functional and work outcomes after an injury, researchers found that 23 percent of injury survivors were continuing to experience PTSD symptoms a year post-injury. 55 In addition, research indicates between 20-50% of trauma patients on surgical wards fit criteria for current or long term substance abuse.…”
Section: Introductionmentioning
confidence: 99%